High‐resolution MR neurography follow‐up of SARS‐CoV‐2 vaccination‐associated neuralgic amyotrophy - Christoph M. Mooshage; Henrich Kele; Martin Bendszus; Daniel Schwarz (Annals of Clinical and Translational Neurology, 2023)
Abstract Little is known about the value of high‐resolution follow‐up imaging in patients with neuralgic amyotrophy (NA) and the question of the best treatment algorithm remains unclear. Three patients (one female, two male) with the clinical presentation of SARS‐CoV‐2‐vaccination‐associated NA underwent initial magnetic resonance neurography (MRN) imaging and follow‐up examinations. All patients showed a marked clinical improvement, independent of treatment, including an almost full recovery of motor function over the course of 8–12 months which was accurately mirrored by imaging findings on MRN. MRN imaging is a valuable tool for monitoring the further clinical course of patients suffering from vaccination‐associated NA.